Pengaruh Hemodialisis Terhadap Kadar Glutation Tereduksi (GSH) Plasma Pasien Hemodialisis RSUD Arifin Ahmad - Hannan Khairu Anami; W. Ristua Butar-Butar; Enikarmila Asni (Jurnal Ilmu Kedokteran, 2011)
Chronic kidney disease patients who received hemodialysis therapy have higher risks to get atherosclerosis, inflammation,and cancer than general population at the same age. Imbalance of free radicals level and antioxidants defense whichdefined as oxidative stres may cause these complications. This study investigated the influence of hemodialysis onreduced glutathione (GSH) level, one of antioxidant, in blood plasma of hemodialysis patient at RSUD Arifin Ahmad.This was a cross sectional study that compare plasma GSH level before and after hemodialysis process. Population ofthis study was 72 patient in RSUD Arifin Ahmad but only 17 patient fulfilled all the inclusion and exclusion criteria.Plasma GSH level was measured by using Ellman method. The result showed that there were no significant differenceof plasma GSH level in patient before and after hemodialysis process (p=0,426).